DETERMINATION OF SOMATIC ANTIGENS AND EXCRETION-SECRETION OF LEISHMANIA PERUVIANA FOR ELECTROBLOTTED USING IGY PRODUCED IN GALLUS GALLUS EXPERIMENTALLY IMMUNIZED - Carranza-Quispe, Luis Emilio (2015)
The purpose of this study was to determine the somatic and excretory-secretory antigens by Leishmania peruviana electroblotted using IgY antibodies produced by immunized experimental Gallus gallus. Antigens were obtained by centrifugation of promastigotes grown at 37 °C for 20 h in Minimun Essential Medium-Eagle (MEM-Sigma), the supernatant containing the excretory secretory antigens and somatic antigens sediment. For the anti-leishmania antibodies IgY, two hens were immunized first with the excretory-secretory antigens and the second with somatic antigens. When faced with L. peruviana antigens with IgY it was noted that somatic antigens produced ten antigenic bands with molecular weights of 10, 12, 17, 20, 31, 38, 69, 87, 93 and 105 kDa; with excretory-secretory antigens nine antigenic bands of molecular weights of 17, 20, 31, 52, 67, 78, 87, 93 and 105 kDa were produced, observing five common antigens 20, 31, 87, 93 and 105. Such somatic and excretory-secretory antigens by promastigotes of L. peruviana that have been detected by electroblotting technique could be used in the future for diagnosis of cutaneous leishmaniasis.